Cover, Content, and Editorial Note from Borneo J Pharm Vol. 4 No. 1 February 2021 - Chief Editor of Borneo J Pharm (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Alhamdulillahirabbil ‘Alamin. The next edition of the Borneo Journal of Pharmacy (Borneo J Pharm), has been published in February 2021. Starting from this edition, Borneo J Pharm increases the frequency of publishing four times a year. This change aims to improve the circulation of the best articles published by Borneo J Pharm. Also, starting from this edition, Borneo J Pharm applying the publish-as-you-go issue to present the title of the article that has been received as early as possible in order to increase the chances of readability and quotation of articles in Borneo J Pharm. This edition includes writings from four countries including Indonesia, India, Malaysia, and Nigeria. The authors come from several institutions, including Universitas Muhammadiyah Palangkaraya, Universitas Muhammadiyah Surakarta, Universitas Muhammadiyah Malang, Universiti Teknologi MARA Cawangan Sarawak, Politeknik Bina Husada Kendari, Universitas Halu Oleo, Akademi Farmasi Surabaya, Universitas Hang Tuah, Universitas Mandala Waluya, Universitas Gadjah Mada, Universitas Abdurrab, Federal University of Technology Minna, Humera Khan College of Pharmacy, University of Abuja, and Universitas Ahmad Dahlan. Editorial boards are fully aware that there is still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank all editors and reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope that all parties, especially the contributors of the articles, could re-participate for publication in the next edition in May 2021.